Multiple antibiotic resistance index of escherichia coli isolated from pig farm waste in Kuching, Sarawak - Ong, Sue Ann (Universiti Malaysia Sarawak, (UNIMAS), 2011)
E. coli has been known as one of the most common bacteria found in the intestinal tract of human and warm blooded animals. Most strains are harmless, however some strains have been identified as the serious causal agents of various illnesses. In this study, out of 47 isolates from samples from three different pig farms located at 10th miles Kuching, only 12 of the isolates were found to be E. coli and 2 out of 12 isolates were identified as EPEC since they were tested positive for Shiga toxin-producing E. coli (STEC) virulence gene stx1 in PCR. Molecular detection was done by PCR and the PCR product was analyzed using 1.0% agarose gel electrophoresis. EMB agar was used to selectively grow E. coli isolated from the pig waste and further identification was carried out through biochemical tests such as IMViC test, S.I.M test and also citrate utilization test. In addition, an antimicrobial susceptibility test had been conducted as to find out the MAR index value of E. coli, it was found that MAR index of E. coli isolated from pig farm waste is significantly high (all above 0.6) and this shows that the pig waste was a high risk sources of contamination which may posed hazard to farmers and the public.